A Comparison of Fully-Coupled 3D In-Stent Restenosis Simulations to In-vivo Data - Zun, Pavel S.; Anikina, Tatiana; Svitenkov, Andrew; Hoekstra, Alfons G. (Frontiers in Physiology, 2017)
We describe our fully-coupled 3D multiscale model of in-stent restenosis, with blood flow simulations coupled to smooth muscle cell proliferation, and report results of numerical simulations performed with this model. This novel model is based on several previously reported 2D models. We study the effects of various parameters on the process of restenosis and compare with in vivo porcine data where we observe good qualitative agreement. We study the effects of stent deployment depth (and related injury score), reendothelization speed, and simulate the effect of stent width. Also we demonstrate that we are now capable to simulate restenosis in real-sized (18 mm long, 2.8 mm wide) vessel geometries.